Novel Generalized Divergence Measure on Intuitionistic Fuzzy Sets and Its Application. (23rd July 2021) - Arora, Priya; Tomar, V. P.
Abstract : In the present paper, we introduce a new parametric fuzzy divergence measure on intuitionistic fuzzy sets. Some properties of the proposed measure are also being studied. In addition, the application of the intuitionistic fuzzy divergence measure in decision making and consequently choosing the best medicines and treatment for the patients has also been discussed. There are some diseases for which vaccine is not available. In that case, we have devised a method to choose the best treatment for the patients based on the results of clinical trials.